Attenuated total reflectance–Fourier transform infrared study of the effects of citrate on the adsorption of phosphate at the hematite surface. Issue 1 (23rd January 2020) - Barreto, Matheus S. C.; Elzinga, Evert J.; Alleoni, Luis R. F.
Abstract: Carboxylic acids affect the retention and solubility of phosphate in soils and rhizospheres, but spectroscopic studies addressing the mechanisms involved are scarce. Here, we used in situ attenuated total reflectance Fourier transform infrared spectroscopy to study the mechanisms of adsorption of orthophosphate and citric acid onto hematite in binary and ternary systems at pH 4.5, 5.5, and 6.5. In binary systems, phosphate adsorbed as a mixture of two inner‐sphere species assigned as monodentate and bridging complexes, with the fraction of bridging species increasing with decreasing pH. Citrate coordinated to the hematite surface through the carboxylate groups, which consisted of a mixture of inner‐sphere complexes and either noncoordinated or outer‐sphere complexes, with inner‐sphere complexation becoming more important at lower pH. Introduction of citrate into pre‐equilibrated phosphate–hematite systems induced desorption of both the monodentate and bridging phosphate species, with competitive effects increasing with decreasing pH. At pH 5.5 and 6.5, the bridging complexes were mobilized to a larger extent than initially present on the surface, indicating preferential desorption. Similarly, pre‐equilibration of hematite with citrate preferentially inhibited the formation of the bridging phosphate surface complexes. Their relatively strong susceptibility to interference by citrate suggests that the bridging phosphate species are protonated monodentate complexes engaged in hydrogen bonding to adjacent surface sites. The results of this study refine our understanding of the mechanisms of phosphate retention at Fe‐oxide mineral surfaces and demonstrate that carboxylic acids may affect not only phosphate solubility but also the speciation of phosphate associated with Fe‐oxides in soil and rhizosphere environments.